A secured distributed detection system based on IPFS and blockchain for industrial image and video data security - Kumar, Randhir; Tripathi, Rakesh; Marchang, Ningrinla; Srivastava, Gautam; Gadekallu, Thippa Reddy; Xiong, Neal N. (Journal of parallel and distributed computing, 2021)
Copyright infringement adversely affects the interest of copyright holders of images and videos which are uploaded to different websites and peer-to-peer image sharing systems. This paper addresses the problem of detecting copyright infringement so that copyright holders are given due credit for their work. There are several images and videos that are shared every day by millions of users with some amount of modification in images and videos originally uploaded by the copyright holders such as photographers, graphic designers, and video providers. Copyright violators, who are not the original creators of multimedia content modify them using image processing and frame modification techniques such as grayscale conversion, cropping, rotation, frame compression, and frame speed manipulation. Then, upload the tampered images and videos. To address this problem, we propose an IPFS-based (InterPlanetary File System-based) decentralized peer-to-peer image and video sharing platform built on blockchain technology. We use a perceptual hash (pHash) technique to detect copyright violations of multimedia. When multimedia is to be uploaded to the IPFS, the pHash of the same content is determined and checked against existing pHash values in the blockchain network. Similarity with existing pHash values would result in the multimedia being detected as tampered with. Blockchain technology offers the advantage of non-involvement of a third party and consequently the avoidance of a single point of failure. •We present a platform of blockchain and IPFS to store multimedia objects as transactions.•The proposed framework ensures multimedia availability, immutability, and transparency.•The proposed approach is fully distributed where copyright information can be verified.